(untitled) (Majalah Kedokteran Bandung, 2022)
Smoking is defined as burning dry tobacco leaves and inhaling smoke from the burn. This process may be done using different forms of tobbaco products, including cigarettes (Cigars, Little Cigars, Cigarillos), electronic cigarettes, and hookah (shisha). Smoking can give rise to lung diseases such as chronic obstructive pulmonary disease (COPD) and has been proven to be the underlying cause in 84% of deaths in lung cancer and 83% mortalities in COPD. This study was conducted to determine the prevalence of tobacco smoking among male students of the Majmaah University, Saudi Arabia. This cross-sectional study was performed from January to February 2020 on among medical students of Majmaah University, Saudi Arabia. A pretested questionnaire was used to collect data while the SPSS was used for data analysis. From 256 male medical students, only 113 responded to the questionnaire. The prevalence of smoking was found to be 19.5% (n=22) with most smoked cigarettes (50%). Most smokers (50 %) were in the lowest age group, 19-21 years. There was an increase in smoking with an increase in income. Of the 22 respondents who smoked, 10 started smoking when they were 14 to 17 years old. In conclusion, the study shows a low prevalence of smoking among male medical students in the College of Medicine of Majmaah University. Most smokers consume cigarettes, and the majority are not considering quitting.